Diphtheria toxin activates ribotoxic stress and NLRP1 inflammasome-driven pyroptosis - Robinson, Kim Samirah (2023)
The ZAKα-driven ribotoxic stress response (RSR) is activated by ribosome stalling and/or collisions. Recent work demonstrates that RSR also plays a role in innate immunity by activating the human NLRP1 inflammasome. Here, we report that ZAKα and NLRP1 sense bacterial exotoxins that target ribosome elongation factors. One such toxin, diphtheria toxin (DT), the causative agent for human diphtheria, triggers RSR-dependent inflammasome activation in primary human keratinocytes. This process requires iron-mediated DT production in the bacteria, as well as diphthamide synthesis and ZAKα/p38-driven NLRP1 phosphorylation in host cells. NLRP1 deletion abrogates IL-1β and IL-18 secretion by DT-intoxicated keratinocytes, while ZAKα deletion or inhibition additionally limits both pyroptotic and inflammasome-independent non-pyroptotic cell death. Consequently, pharmacologic inhibition of ZAKα is more effective than caspase-1 inhibition at protecting the epidermal barrier in a 3D skin model of cutaneous diphtheria. In summary, these findings implicate ZAKα-driven RSR and the NLRP1 inflammasome in antibacterial immunity and might explain certain aspects of diphtheria pathogenesis.